Physiological affinities in some filamentous fungi Environment - Gardini, W. E: (1965)
Has been isolated from the environment 14 groups of pollutants filamentous fungi using the agar medium fresh tomato . They investigated faith selective reactions carbohydrates fermentation to 18 , their mutual reactions and production of deoxyribonuclease ( DNase ) . Was found to have a preference for certain ferment carbohydrates such as sucrose , galactose, mannose , maltose , raffinose, melibiose , by Aspergillus fumigatus , Aspergillus nigricana , Aspergillus ochraceus , Aspergillus oryzae , Alternaria , CunninghameIla , clades Porium herbarum , Fusarium roseum , Glenospora , Hormodendrum , bicolor Penicillium , Penicillium sp. ACI -9 strain , Rhizopus and Trichophyton sp. That varieties of fungi within the same genus have different fermentative power as with the Aspergillus fumigatus , Aspergillus nigricans , Aspergillus ochraceus and Aspergillus ONZAE on the adonitol , arabinose , dulcitol and melezitose . 14 environmental groups have produced DNase filamentous fungi using as a culture medium tryptose agar - deoxyribonucleic acid as reagent and methyl green dye . The variety of Penicillium , ACI -9 strain , low fermentative power of about 18 most carbohydrates presented inhibitory potential on Aspergillus desorrollo nigricans , Aspergillus ochraceus , Alternaria , Blastomyces dermatitidis , and to a greater degree on Aspergillus fumigatus , Aspergillus oryzae , CunninghamelIa , Penicillium and Rhizopus bicolor.